Effect of Vitamin D3 on Caspase-3 Expression of Retinal Ganglion Cell Wistar Rats with N-Methyl-D-Aspartate-induced Model of Glaucoma - Maharani; Winarto; Hermawan; Mahanani, Seia; Saubig, Arnila Novitasari; Dharma, Andhika Guna (Majalah Oftalmologi Indonesia, 2023)
Introduction & ObjectivesIntroduction: Vitamin D is a neuroprotective neurosteroid hormone with antioxidant, antiinflammatoryand anti-ischemic properties that can reduce the entry of intracellular calcium,thereby reducing cytochrome-c, modulating inflammation, increasing Nitric Oxide production bysuppressing oxidative stress and activating caspase-3 activation. Excitotoxicity due to N-Methyl-DAspartatecauses caspase-3 activation due to increased calcium in cells and describes thepathogenesis of vascular factor glaucoma due to retinal ganglion cell (RGC) damage in the absenceof an increase in intraocular pressure. RGC damage can be assessed by the expression of caspase-3which is a proapoptotic agent that acts as the main effector caspase in the mechanism of apoptosis.Objective: Proving the effect of vitamin D3 on caspase-3 expression of retinal ganglion cells wistarrats in NMDA-induced glaucoma models. MethodsAn experimental study, using post-test only randomized controlled group design, was done on 14male NMDA-induced glaucoma wistar rats, divided into 2 groups. The treatment group was givenoral vitamin D3 500 IU/kgBW every 24 hours for 10 weeks, while the control group was givenaquadest. Immunohistochemistry was used to measured caspase-3 expression. Mann-Whitneyanalized non-parametric difference test (Significant p<0.05). ResultsCaspase-3 expression of retinal ganglion cell was significantly lower (p=0.004) in treatment group(mean=5,29 ± 0,76) compared to control group (mean=6,71 ± 0,49). ConclusionOral vitamin D3 has an effect on caspase-3 expression of retinal ganglion cells wistar rats in NMDAinducedglaucoma models. Further research is needed to investigate the protective role of vitaminD3 on glaucoma patients.